Economic Impacts of SECA Regulation on Maritime Companies in the Baltic Sea Region – Literature Review and Low Emissions Recommendations: Part 2 - Esa Hämäläinen; Tommi Inkinen (Serbia, 2025)
This is the second part of our research. Two publication databases were queried: Science Direct (SD) and Web of Science (WoS). The search query in these channels was performed using keywords “SECA, economic impacts” to investigate how SECA implications were studied for clean business development. Two main topic groups were discovered. The first group includes topics that focus on solving negative impacts (economy of maritime businesses); and the second group consists of topics that focus on the positive impacts on health and the environment, particularly in SECA port regions. After the screening process, the data included 21 papers that matched the query specifications. The decision was made to only use the most recent studies that were completed after 2015. The results indicate that ship owners and fuel producers can use various methods simultaneously to adapt to the SECA regulation.
Proceedings of the 4th Logistics International Conference